Distinctive Paradigm of Maqasid Syari'ah and Maqasid Al-Qur'an - Saiful Hidayat (Al-'Allāmah: Journal of Scriptures and Ulama Studies, 2024)
The existence of maqasid al-Qur'an cannot be separated from the discussion of maqasid al-syari'ah which was previously known in the treasures of Islamic scholarship. However, of course there are differences between the two terms which are certainly interesting to discuss. This paper tries to uncover the actual differences between the two terms above. So the author tries to discuss the definitions of both, then tries to uncover their genealogy. After that, the author took photos of the characters who discussed the maqasid of the Sharia and the maqasid of the Qur'an so that they could clearly illustrate what was discussed in these two things. It turns out that there are several fundamental differences between the two sciences, both in terms of definition, genealogy, discussion and reference sources. However, there are also many similarities in them, or at least a close connection between the two.